Application of wordwall media in PPKn learning for grade IV elementary school students: a qualitative study - Jeni Puspitasari; Sukartono Sukartono (Lembaran Ilmu Kependidikan, 2025)
Background - PPKn learning has an important role in shaping students' character, but conventional methods often make them passive and less motivated. Therefore, learning innovation is needed by utilizing interactive digital media so that students are more active and understand the material better. Purpose - This study aims to describe the application of wordwall media in learning Pancasila and Citizenship Education (PPKn) in grade IV of SD Muhammadiyah Plus Malangjiwan Colomadu. Wordwall is a digital-based learning media that allows teachers to create interactive activities such as quizzes, matching, and other educational games to increase student engagement and understanding of the subject matter. Method/approach - This study uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. To ensure the validity of the data, triangulation of techniques and sources is used. Meanwhile, data analysis is carried out through three main stages, namely data presentation, data reduction, and verification or drawing conclusions. Findings - The results of the study show that in learning planning, teachers rarely create teaching modules or RPPs so that they only compile them when there are administrative needs. The use of wordwall in PPKn learning has a significant impact on student engagement, where students become more active in discussions, show increased enthusiasm in answering questions, and understand the concepts taught more easily. Compared to the lecture method, student engagement increased substantially, with most students showing active participation during the learning process. Supporting factors in the implementation of this media include adequate internet access and the availability of devices such as projectors and speakers. Conclusions - However, there are several obstacles such as limited time for teachers to create media, minimal teacher skills in using technology, and technical obstacles such as unstable electricity.  As a solution, training and assistance are needed for teachers in utilizing digital-based media in order to optimize learning, as well as arranging the schedule for using projectors or increasing the capacity of electricity to overcome technical obstacles. Novelty/Originality/Value - The implication of this study is that the integration of digital media such as wordwall in PPKn learning not only increases student engagement but also encourages innovation in teaching methods, so teachers need to develop their digital competencies to create more engaging and effective learning.